OP16 Do financial strain and labour force status explain why Nordic countries have wide health inequalities relative to other European countries? Evidence from a cross-national study. (2nd September 2014) - Shaw, RJ; Benzeval, M; Popham, F
Abstract : Background: A major puzzle is why Nordic countries do not have the smallest health inequalities despite having relatively egalitarian social policies. The aim of this paper is to investigate whether important drivers of class differences in health such as financial strain and labour force status account for the social patterning of health in Nordic countries to a similar degree to other European countries with different welfare regimes. Methods: Our analyses used data for men (n = 48, 249) and women (n = 52, 654) aged between 25 and 59 for 20 countries from five rounds (2002–2010) of the European Social Survey which is a nationally representative repeated multinational cross sectional survey. The main outcome was self-rated health in 5 categories. Using separate models by country and gender and adjusting for survey round we used linear regression to investigate the degree to which class inequalities – comparing working to professional occupations using the European Socio-Economic Classification – were attenuated by financial strain and labour force status. Results: Before adjustment, Nordic countries had comparatively large inequalities in self-rated health relative to other European countries. For example the linear regression coefficient for the difference in health between working class and professional men living in Norway was 0.33 (95% CI 0.25–0.4), while the comparable figure for Spain was 0.16 (95% CI 0.09–0.23). Adjusting for financial strain and labour force status lead to attenuation of health inequalities for all countries. However, unlike some countries such as Spain where after adjustment the regression coefficient for working class men was only 0.04 (95% CI -0.04 to 0.11), health inequalities persisted after adjustment for Nordic countries. For example the adjusted coefficient for Norway was 0.16 (95% CI 0.09 to 0.24). The effects of survey round were very small and non-significant for most countries. Rerunning the analyses using ordinal logistic regression did not substantively change the results. Results for women and men were similar. However, in comparison to men, class inequalities tended to be stronger for women and financial strain and labour force status explained a lower proportion of health inequalities for countries in all welfare regimes. Conclusion: Adjusting for financial security and labour force status attenuates a high proportion of health inequalities in some counties, particularly Southern European countries, but attenuation in Nordic countries is modest. To address class inequalities in Nordic countries policies need to focus on other mechanisms.